2021
DOI: 10.1200/jco.21.00396
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine Plus Cisplatin Versus Fluorouracil Plus Cisplatin as First-Line Therapy for Recurrent or Metastatic Nasopharyngeal Carcinoma: Final Overall Survival Analysis of GEM20110714 Phase III Study

Abstract: PURPOSE GEM20110714 (ClinicalTrials.gov identifier: NCT01528618 ), the first randomized, phase III study of systemic chemotherapy in recurrent or metastatic nasopharyngeal carcinoma (NPC), reported significant progression-free survival improvement with gemcitabine plus cisplatin (GP) versus fluorouracil plus cisplatin (FP; hazard ratio, 0.55; 95% CI, 0.44 to 0.68; P < .001). Data from the final analysis of overall survival (OS) are presented here. METHODS From February 2012 to October 2015, 362 patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 34 publications
(46 reference statements)
0
51
1
Order By: Relevance
“…These include compounds that target enzymes implicated in epigenetic pathways as Histone Deacetylase (HDAC), DNA methyltransferase (DNMT), Euchromatic histone lysine methyltransferase 2 (EHMT2) or G9a [ 8 ], and Sirtuins (SIRT) [ 9 ]. They could represent promising new therapeutic targets for the treatment of PDAC [ 10 ], either alone or in combination with gemcitabine [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…These include compounds that target enzymes implicated in epigenetic pathways as Histone Deacetylase (HDAC), DNA methyltransferase (DNMT), Euchromatic histone lysine methyltransferase 2 (EHMT2) or G9a [ 8 ], and Sirtuins (SIRT) [ 9 ]. They could represent promising new therapeutic targets for the treatment of PDAC [ 10 ], either alone or in combination with gemcitabine [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Except of the first prospective trial in pediatric NPC by Ghim, reported in 1998, this combination has been used in all other prospective studies of pediatric patients with nasopharyngeal carcinoma, with some studies adding a third agent such as methotrexate or docetaxel [ 3 , 4 , 17 , 18 , 26 , 27 , 33 , 34 ]. Recently, a large randomized trial in adults has shown a significant benefit for the combination of gemcitabine/cisplatin (GP) versus 5-fluoruracil/cisplatin (PF) in patients with NPC and distant metastases or refractory disease [ 35 , 36 ]. However, in adult patients with locoregionally advanced NPC, GP, and PF have so far only been compared in smaller phase II trials, without showing a clear benefit toward one regimen [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current NCCN Head and Neck Cancer Clinical Practice Guidelines® recommend gemcitabine plus cisplatin (category 1 recommendation) as the preferred first-line systemic therapy for RM-NPC [4]. Although standard-of-care (SOC) gemcitabine plus cisplatin can provide clinical benefit in RM-NPC, it is not effective in many patients or only provides short-lived benefit (per the phase 3 GEM20110714 study: objective response rate [ORR], 64%; median progression-free survival [PFS], 7.0 months; and median overall survival [OS], 22.1 months) [8,9]. Accordingly, novel treatment options are needed to improve outcomes for patients with RM-NPC.…”
Section: Current Treatment Landscape and Unmet Needmentioning
confidence: 99%